2017
DOI: 10.1123/jpah.2017-0090
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Meeting 24-Hour Movement Guidelines and Cardiometabolic Risk Factors in Children

Abstract: Background The purpose was to evaluate the relationship between adherence to pediatric 24-hour movement guidelines (moderate-to-vigorous physical activity (MVPA), sedentary behavior and sleep) and cardiometabolic risk factors. Methods The sample included 357 white and African American children aged 5-18 years. Physical activity, TV viewing and sleep duration were measured using questionnaires, and the 24-hour guidelines were defined as: ≥60 min/day of MVPA on ≥5 days/week, ≤2 h/day of TV, and sleeping 9-11 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
79
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 21 publications
12
79
3
2
Order By: Relevance
“…A previous study including children from different continents, demonstrated that meeting integrated guidelines was associated with the lowest odds ratio of obesity when compared with meeting individual or no guidelines [19]. Similar findings have also been reported in a study of American children [44]. Despite this evidence for the importance of considering all MBs, to our knowledge no study has examined the adherence to 24-Hour Movement Guidelines among children at similar age as in our study.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study including children from different continents, demonstrated that meeting integrated guidelines was associated with the lowest odds ratio of obesity when compared with meeting individual or no guidelines [19]. Similar findings have also been reported in a study of American children [44]. Despite this evidence for the importance of considering all MBs, to our knowledge no study has examined the adherence to 24-Hour Movement Guidelines among children at similar age as in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Too little sleep, too little physical activity, and too much sedentary time have been associated with poor physical and mental health outcomes. These outcomes have included increased risk of obesity, impaired glucose metabolism, cardiovascular disease, depression and anxiety [2][3][4]. In recognition of the combined importance of sleep, physical activity and sedentary behaviours, Canada [5] and Australia have recently published 24-h 'movement' guidelines for children aged 5 to 17.…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that those who were reaching the comprehensive movement assessment and its components would have a greater likelihood of being MHO compared to Non-MHO adults. Although previous studies have looked at the associations between meeting comprehensive movement guidelines and the likelihood of obesity 27,28 , this is the first study, to the best of our knowledge, to apply a comprehensive movement assessment to a sample of overweight and obese adults using the MHO phenotype as an outcome. The current study has many relevant results from a cardiometabolic perspective.…”
Section: Discussionmentioning
confidence: 99%